Social Media Retrieval and Mining ADMA 2012 Workshops, SNAM 2012 and SMR 2012, Nanjing, China, December 15-18, 2012. Revised Selected Papers - Zhou, Shuigeng; Wu, Zhiang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the ADMA 2012 Workshops: The International Workshop on Social Network Analysis and Mining, SNAM 2012, and the International Workshop on Social Media Mining, Retrieval and Recommendation Technologies, SMR 2012, Nanjing, China, in December 2012. The 15 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on networks and graphs processing; social Web; social information diffusion; social image retrieval and visualization.
Networks and graphs processing -- Social Web -- Social information diffusion -- Social image retrieval and visualization.
Keywords: Computer science; Data mining; Information storage and retrieval; Application software; Computer Science; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Computer Appl. in Social and Behavioral Sciences; Electronic books